Revisting the relationship between income, inequality and economic growth (2006)
Introduction Acopious literature on the relationship between income distribution and economic growth has been developed recently and particularly during the 1990s. Among this literature animportant branch has focused on developing theoretical models to posit and explore a causal relationship that, contrary to the traditional Kuznets' curve literature, goes from inequality to growth. :N lost of these models put forward the existence of a negative correlation between inequality and growth that operates through a myriad of mechanisms. In a related effort, a number of studies have attempted to empirically estimate this relationship by means of different modeling approaches. A broad consensus validating the existence of this negative correlation prevailed until some authors began usingpanel data estimation techniques that have tended to show a positive correlation